Development of an ideological and political education design based on course characteristics: taking high performance liquid chromatography as an example - YANG, Huili; TANG, Gangfeng; LEI, Jie (Se pu = Chinese journal of chromatography, 2025)
In response to the problems of the easy repetition of ideological and political education cases and the difficulty of evaluating ideological and political education, this study takes the classic experimental method of high performance liquid chromatography as an example to carry out the teaching practice of ideological and political education based on the characteristics of the course. First, the aim of the experiment, that is, the determination of preservatives and sweeteners in food, was introduced. Next, the specific practice processes, including case significance, case introduction, case implementation, case expansion, and effectiveness assessment, of two types of ideological and political programs, namely, universal and specialized cases, were introduced. Universal cases consider the importance of instrumental analytical experiments, while specialized cases consider the localization of high performance liquid chromatographs. We adjusted the ideological and political content of the instrumental analytical experimental course according to the course progress and actual experience of students, and integrated ideological and political education into the curriculum in stages. In addition to the functions of value guidance and ideological education, the role of ideological and political programs in promoting professional knowledge learning and innovation ability training was strengthened. We recommend that the effectiveness of ideological and political education be evaluated by mastering professional knowledge and improving innovative abilities.